Analisa Kondisi Lingkungan Di PT. X - Ambarwati, Nandia Rian; Sasmita, Aryo; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
PT. X in its operational activities has the potential to generate noise coming from palm oil production machines. Workers who are constantly exposed to noise have the potential to affect their health and comfort. The purpose of this research is to know the intensity of noise generated by oil palm production machine, exposure time, mapping of noise distribution pattern, and noise control effort. Meteorological data includes temperature, humidity, wind speed and wind direction. Meteorological data includes temperature, humidity, wind speed and wind direction. From the measurement results of the area temperature 38 0C, while for the ISBB (wet ball temperature index) conditions at the work location must not exceed 26.7 Â° C. measurement of air humidity is 80.2%, and for the provision of humidity levels of air humidity in the work environment up to 90% can be tolerated. And the results of the measurement of wind speed obtained are 1.1 m / s for wind speed itself is one of the medium of sound mediation. Keyword : Wind speed, air humidity, temperature